Simultaneous Disruption of Mouse ASIC1a, ASIC2 and ASIC3 Genes Enhances Cutaneous Mechanosensitivity - Kang, Sinyoung; Jang, Jun Ho; Price, Margaret P.; Gautam, Mamta; Benson, Christopher J.; Gong, Huiyu; Welsh, Michael J.; Brennan, Timothy J. (PLOS ONE, 2012)
Three observations have suggested that acid-sensing ion channels (ASICs) might be mammalian cutaneous mechanoreceptors; they are structurally related to Caenorhabditis elegans mechanoreceptors, they are localized in specialized cutaneous mechanosensory structures, and mechanical displacement generates an ASIC-dependent depolarization in some neurons. However, previous studies of mice bearing a single disrupted ASIC gene showed only subtle or no alterations in cutaneous mechanosensitivity. Because functional redundancy of ASIC subunits might explain limited phenotypic alterations, we hypothesized that disrupting multiple ASIC genes would markedly impair cutaneous mechanosensation. We found the opposite. In behavioral studies, mice with simultaneous disruptions of ASIC1a, -2 and -3 genes (triple-knockouts, TKOs) showed increased paw withdrawal frequencies when mechanically stimulated with von Frey filaments. Moreover, in single-fiber nerve recordings of cutaneous afferents, mechanical stimulation generated enhanced activity in A-mechanonociceptors of ASIC TKOs compared to wild-type mice. Responses of all other fiber types did not differ between the two genotypes. These data indicate that ASIC subunits influence cutaneous mechanosensitivity. However, it is unlikely that ASICs directly transduce mechanical stimuli. We speculate that physical and/or functional association of ASICs with other components of the mechanosensory transduction apparatus contributes to normal cutaneous mechanosensation.